High-porosity high-strength silicon-based ceramic, preparation method and application thereof, and removal method of ceramic core for titanium alloy casting

By using silica, kaolin and calcium hydroxide to prepare high porosity and high strength silicon-based ceramics, and spraying yttrium oxide coating on its surface, the problem of low strength of silicon-based ceramic cores at high temperatures and reaction with titanium alloys is solved. , realizes efficient ceramic core removal and titanium alloy blade production.

CN119390458AActive Publication Date: 2025-02-07CENT SOUTH UNIV +1

Patent Information

Application Number
CN202411524374.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing silicon-based ceramic cores have low strength, high deformation at high temperatures and react with titanium alloys, which affect the production pass rate and cost of titanium alloy blades.

Method used

Silica, kaolin and calcium hydroxide are used as raw materials to prepare high porosity and high strength silicon-based ceramics by mixing powder, ball milling, adding binder and pressing and sintering, and spraying yttrium oxide coating on its surface to improve Chemical reactions are inert.

Benefits of technology

The room temperature and high temperature bending strength of the silicon-based ceramic core is improved, the porosity and dissolution performance are improved, the reaction with titanium alloy is reduced, and the effective removal of the ceramic core is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390458A_ABST
    Figure CN119390458A_ABST
Patent Text Reader

Abstract

The invention provides a high-porosity and high-strength silicon-based ceramic, a preparation method and application thereof, and a removal method of a ceramic core for a titanium alloy casting, the silicon-based ceramic comprises the following raw materials: solid powder and a binder, the solid powder comprises 60-100 wt% of silicon dioxide, 0-20 wt% of kaolin, and 0-20 wt% of calcium hydroxide; wherein the content of kaolin is greater than 0, and the content of calcium hydroxide is greater than 0; the mass ratio of the solid powder to the binder is 1: (0.01-0.05); the silicon dioxide is taken as a raw material, and the kaolin and calcium hydroxide powder are taken as mineralizers, so that the sintering of the material and the generation of christobalite can be effectively promoted, the open porosity of the silicon-based ceramic is improved, the collapsibility is improved, and meanwhile, a new phase is formed and is mutually combined to form a framework so as to enhance the mechanical property of the silicon-based ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic cores for titanium alloy casting, and more specifically, to a high-porosity and high-strength silicon-based ceramic, a preparation method and application thereof, and a method for removing a ceramic core for titanium alloy castings. Background Art

[0002] The hollow blades of aircraft engines and gas turbines are precision parts that are subjected to high temperature and high pressure conditions on the turbine rotor at the rear end of the calcination chamber. They are usually manufactured using alloy melt casting technology. The template material of the hollow part of the hollow blade is called a ceramic core, which is a prefabricated part that needs to be formed and sintered before casting. It needs to be pre-filled into the ceramic shell to provide shape stability and high-temperature mechanical properties during casting. After casting, the ceramic core is removed by chemical methods to form a hollow blade. The dimensional stability and mechanical properties of the ceramic core are key auxiliary materials that determine whether the hollow cavity of the blade can be successfully generated and provide a continuous airflow channel. It is one of the high-end and key products of ceramic products for precision casting.

[0003] At present, the ceramic cores used at home and abroad are mainly aluminum-based ceramic cores and silicon-based ceramic cores. Aluminum-based ceramic cores have better thermal strength and thermal stability, and are structurally stable during sintering and use, have no high and low temperature crystal transformation, and have good high temperature resistance. However, it is difficult to de-core aluminum-based ceramic cores, which inhibits their widespread practical application and development. Compared with aluminum-based ceramic cores, silicon-based ceramic cores have the advantages of low sintering temperature, better controllability of quartz conversion rate, small thermal expansion coefficient, and good de-core performance. However, silicon oxide-based cores also generally have problems such as low high temperature strength, large deformation, and reaction with titanium alloys, which affect the production qualification rate and cost of alloy blades. Summary of the invention

[0004] Based on the above technical problems existing in the prior art, the present invention provides a high-porosity and high-strength silicon-based ceramic. The raw materials of the silicon-based ceramic include solid powder and a binder. The silicon-based ceramic uses silicon dioxide as a raw material and kaolin and calcium hydroxide as mineralizers, and has the characteristics of high porosity and high strength.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] A high-porosity and high-strength silicon-based ceramic, the raw materials of which include solid powder and a binder, and the solid powder is composed of the following components:

[0007] Silicon dioxide 60-100wt%

[0008] Kaolin 0-20wt%

[0009] Calcium hydroxide 0-20wt%;

[0010] Among them, the content of kaolin is greater than 0, and the content of calcium hydroxide is greater than 0;

[0011] The mass ratio of the solid powder to the binder is 1:0.01-0.05.

[0012] In some embodiments, the average particle size of the silicon dioxide is 25-40 μm; the average particle size of the kaolin is 0.5-5 μm; and the average particle size of the calcium hydroxide is 0.5-2 μm.

[0013] The present invention also provides a method for preparing the silicon-based ceramic according to any of the above embodiments, the method comprising the following steps:

[0014] Silicon dioxide, kaolin and calcium hydroxide powders are mixed evenly to obtain a mixed powder; then a binder aqueous solution is added and mixed evenly; then the mixture is placed in a mold and pressed to obtain a green body; after the green body is dried, it is sintered to obtain a silicon-based ceramic.

[0015] In some embodiments, the sintering temperature is 1250-1450°C.

[0016] In some embodiments, the sintering time is 3-6 hours.

[0017] In some embodiments, the binder is polyvinyl alcohol; and the concentration of the binder aqueous solution is 3-10 wt %.

[0018] In some embodiments, the solid-to-liquid ratio of the mixed powder to the binder aqueous solution is 15-20 g:1-3 mL.

[0019] In some embodiments, the preparation method comprises the following steps:

[0020] S1. Mix silicon dioxide powder, kaolin powder and calcium hydroxide powder evenly, and fully dry them at a temperature of 100-120°C;

[0021] S2, ball milling the dried powder to obtain a mixed powder; wherein the ball-to-powder ratio is 2:1;

[0022] S3, adding a binder solution to the mixed powder, mixing evenly and passing through a 100 mesh sieve; wherein the solid-liquid ratio is 15-20g:1-3mL;

[0023] S4, taking the powder under the sieve and placing it in a mold for pressing, the pressure used is 3-10MPa, and the holding time is 30-60s to obtain a green body;

[0024] S5, fully drying the green body at a temperature of 100-120° C.;

[0025] S6. Place the dried green body in a muffle furnace and sinter it at a temperature of 1250-1450° C. to obtain silicon-based ceramics.

[0026] The present invention also provides a ceramic core for titanium alloy casting, the ceramic core comprising a silicon-based ceramic and a coating on the silicon-based ceramic, the silicon-based ceramic being any of the silicon-based ceramics described above or a silicon-based ceramic obtained by the preparation method of any of the silicon-based ceramics described above; the coating comprising yttrium oxide.

[0027] In some embodiments, the thickness of the coating is >100 nm; preferably, 150-300 μm; more preferably, 150-250 μm.

[0028] The present invention also provides a method for preparing a ceramic core for titanium alloy casting, the method comprising the following steps:

[0029] The silicon-based ceramic is prepared according to any of the preparation methods described above, and then an yttrium oxide coating is sprayed on the surface of the silicon-based ceramic to obtain the ceramic core.

[0030] In some embodiments, a yttria coating is sprayed on the surface of the silicon-based ceramic by a plasma spraying method to obtain the ceramic core.

[0031] The present invention also provides a method for removing the ceramic core for titanium alloy casting, the method comprising the following steps:

[0032] (1) using the ceramic core for titanium alloy casting or the ceramic core obtained by the method for preparing the ceramic core for titanium alloy casting as a template to cast a titanium alloy to obtain a casting;

[0033] (2) boiling the casting with the ceramic core in a mixed alkali solution and simultaneously performing ultrasonic treatment on the casting;

[0034] (3) After cooling, take out the casting and soak it in water to remove the residual alkali solution;

[0035] (4) immersing the casting treated in step (3) in a hydrochloric acid solution containing a corrosion inhibitor, reacting at a temperature of 80-100° C., and simultaneously performing ultrasonic treatment;

[0036] (5) Repeat steps (2) to (4) until the ceramic core is completely removed.

[0037] In some embodiments, the mixed alkali solution includes 30-60 wt % potassium hydroxide and 5-15 wt % sodium carbonate.

[0038] In some embodiments, the corrosion inhibitor is at least two of copper salts, molybdates, tungstates, zinc salts, potassium iodate, tropaeolum orange, quaternary ammonium salts, Mannich base, hexadecyltrimethylammonium bromide, sodium lauroylamino acid, and sodium dodecyl sulfate.

[0039] In some embodiments, in step (2), the casting with the silicon-based ceramic core is boiled in the mixed alkali solution for 12-36 hours at a natural atmospheric pressure.

[0040] In some embodiments, in step (4), the concentration of the hydrochloric acid solution is ≤6 mol / L; preferably, 4-6 mol / L.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The silicon-based ceramic of the present invention uses silicon dioxide as a raw material, and adopts kaolin and calcium hydroxide powder as mineralizers, which can effectively promote the sintering of the material and the formation of cristobalite, increase the open porosity of the silicon-based ceramic core, improve the collapsibility, and simultaneously form a new phase, which combines with each other to form a skeleton to enhance the mechanical properties of the ceramic core; the silicon-based ceramic is used as a ceramic core for titanium alloy casting, and yttrium oxide is used as a coating on its surface, which can effectively improve the chemical reaction inertness between the ceramic core and the titanium alloy.

[0043] The method for preparing silicon-based ceramics provided by the present invention enables the obtained silicon-based ceramics to have excellent room temperature high temperature bending strength, high porosity and good dissolution performance.

[0044] The ceramic core removal method provided by the present invention inhibits the reaction between hydrochloric acid and titanium alloy under the conditions of high temperature and high concentration hydrochloric acid solution, and can effectively remove the ceramic core while avoiding damage to the titanium alloy during the core removal process. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is the XRD pattern of the silicon-based ceramic core for titanium alloy casting prepared in Example 1 of the present invention;

[0046] Figure 2 This is a SEM image of the fracture of the silicon-based ceramic core prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0047] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0049] Example 1

[0050] The preparation of silicon-based ceramics comprises the following steps:

[0051] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 17:1:2. Mix and fully dry in an oven at 120°C.

[0052] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain a ceramic core mixed powder, with a ball-to-material ratio of 2:1;

[0053] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve;

[0054] S4, weighing a certain mass of the powder under the sieve and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60s to obtain a green body;

[0055] S5. The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered into silicon-based ceramic at 1300° C.

[0056] The XRD analysis spectrum and SEM image of the silicon-based ceramic prepared in this embodiment are shown as follows: Figure 1 and Figure 2 shown.

[0057] Comparative Example 1

[0058] The preparation of silicon-based ceramics comprises the following steps:

[0059] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 19.5:0.5:0, mix and fully dry in an oven at 120°C;

[0060] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain a ceramic core mixed powder, with a ball-to-material ratio of 2:1;

[0061] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve;

[0062] S4, weighing a certain mass of the sieve-under powder and placing it in a mold for pressing, the pressure used is 6-12 MPa, and the pressure holding time is 30-60 s to obtain a green body;

[0063] S5. The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. to obtain silicon-based ceramics.

[0064] Comparative Example 2

[0065] The preparation of silicon-based ceramics comprises the following steps:

[0066] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 19:1:0, mix and fully dry in an oven at 120°C;

[0067] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain a ceramic core mixed powder, with a ball-to-material ratio of 2:1;

[0068] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve;

[0069] S4, weighing a certain mass of the sieve powder and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0070] S5. The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. to obtain silicon-based ceramics.

[0071] Comparative Example 3

[0072] The preparation of silicon-based ceramics comprises the following steps:

[0073] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 18:2:0, mix and fully dry in an oven at 120°C;

[0074] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain a ceramic core mixed powder, with a ball-to-material ratio of 2:1;

[0075] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve;

[0076] S4, weighing a certain mass of the sieve powder and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0077] S5. The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. to obtain silicon-based ceramics.

[0078] Comparative Example 4

[0079] The preparation of silicon-based ceramics comprises the following steps:

[0080] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 18:1:1. Mix and fully dry in an oven at 120°C.

[0081] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain a ceramic core mixed powder, with a ball-to-material ratio of 2:1;

[0082] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve;

[0083] S4, weighing a certain mass of the sieve powder and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0084] S5. The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. to obtain silicon-based ceramics.

[0085] Comparative Example 5

[0086] The preparation of silicon-based ceramics comprises the following steps:

[0087] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 16:1:3. Mix and fully dry in an oven at 120°C.

[0088] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain ceramic core powder, with a ball-to-material ratio of 2:1;

[0089] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100 mesh sieve;

[0090] S4, weighing a certain mass of the sieve powder and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60 seconds to obtain a green body;

[0091] S5. The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. to obtain silicon-based ceramics.

[0092] Comparative Example 6

[0093] The preparation of silicon-based ceramics comprises the following steps:

[0094] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 15:1:4. Mix and fully dry in an oven at 120°C.

[0095] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain a ceramic core mixed powder, with a ball-to-material ratio of 2:1;

[0096] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve;

[0097] S4, weighing a certain mass of the powder under the sieve and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60s to obtain a green body;

[0098] S5. The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered at 1300° C. to obtain silicon-based ceramics.

[0099] Example 2

[0100] The preparation of a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0101] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 17:1:2. Mix and fully dry in an oven at 120°C.

[0102] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain a ceramic core mixed powder, with a ball-to-material ratio of 2:1;

[0103] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve;

[0104] S4, weighing a certain mass of the powder under the sieve and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60s to obtain a green body;

[0105] S5, transferring the green body into an oven at 100° C. for drying; placing the dried green body in a muffle furnace and sintering it into silicon-based ceramic at 1300° C.;

[0106] S6. A 200 μm yttria coating is sprayed on the surface of the silicon-based ceramic by a plasma spraying method to obtain a silicon-based ceramic core for titanium alloy casting.

[0107] Comparative Example 7

[0108] The preparation of a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0109] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 17:1:2. Mix and fully dry in an oven at 120°C.

[0110] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain a ceramic core mixed powder, with a ball-to-material ratio of 2:1;

[0111] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve;

[0112] S4, weighing a certain mass of the powder under the sieve and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60s to obtain a green body;

[0113] S5, transferring the green body into an oven at 100° C. for drying; placing the dried green body in a muffle furnace and sintering it into silicon-based ceramic at 1300° C.;

[0114] S6. A 100 μm yttria coating is sprayed on the surface of the silicon-based ceramic by a plasma spraying method to obtain a silicon-based ceramic core for titanium alloy casting.

[0115] Comparative Example 8

[0116] The preparation of a silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0117] S1. Weigh 20 g of silicon dioxide, kaolin and calcium hydroxide powder in order to ensure that the mass ratio is 17:1:2. Mix and fully dry in an oven at 120°C.

[0118] S2, the dried powder is transferred into a ball mill for ball milling for 10-16 hours to obtain a ceramic core mixed powder, with a ball-to-material ratio of 2:1;

[0119] S3, add 1-3mL of 3-10wt% polyvinyl alcohol aqueous solution to the mixed powder, mix well and pass through a 100-mesh sieve;

[0120] S4, weighing a certain mass of the powder under the sieve and placing it in a mold for pressing, the pressure used is 3-10MPa, and the pressure holding time is 30-60s to obtain a green body;

[0121] S5. The green body is transferred into an oven at 100° C. for drying; the dried green body is placed in a muffle furnace and sintered into silicon-based ceramic at 1300° C.

[0122] S6. A 300 μm yttria coating is sprayed on the surface of the silicon-based ceramic by a plasma spraying method to obtain a silicon-based ceramic core for titanium alloy casting.

[0123] Example 3

[0124] The removal of silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0125] (1) using the silicon-based ceramic core prepared in Example 2 as a template to perform titanium alloy simulation casting to obtain a casting;

[0126] (2) immersing the casting in a mixed solution containing 50 wt% potassium hydroxide and 10 wt% sodium carbonate and boiling for 8 h at a natural atmospheric pressure, while ultrasonically subjecting the casting;

[0127] (3) Take out the casting and soak it repeatedly in deionized water to remove the residual alkali solution;

[0128] (4) immersing the castings soaked in deionized water in a hydrochloric acid solution containing copper chloride and nasturtium orange, keeping the temperature at 90° C. for 4 h, and simultaneously performing ultrasonic treatment on the castings; wherein the concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10 g / L, 1 mmol / L, and 6 mol / L, respectively;

[0129] (5) The casting is taken out and repeatedly soaked in deionized water, and then placed in a mixed solution containing 50wt% potassium hydroxide and 10wt% sodium carbonate and boiled for 8h. The casting is alternately treated with alkaline and acid solutions until the core is completely removed.

[0130] Comparative Example 9

[0131] The removal of silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0132] (1) using the silicon-based ceramic core prepared in Example 2 as a template to perform titanium alloy simulation casting to obtain a casting;

[0133] (2) immersing the casting in a mixed solution containing 50 wt% potassium hydroxide and 10 wt% sodium carbonate and boiling for 8 h at a natural atmospheric pressure, while ultrasonically subjecting the casting;

[0134] (3) Take out the casting and soak it repeatedly in deionized water to remove the residual alkali solution;

[0135] (4) immersing the casting treated in step (3) in a hydrochloric acid solution containing copper chloride and nasturtium orange, keeping the temperature at 90° C. for 4 hours, and simultaneously performing ultrasonic treatment on the casting; wherein the concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10 g / L, 1 mmol / L, and 3 mol / L, respectively;

[0136] (5) The casting is taken out and repeatedly soaked in deionized water, and then placed in a mixed solution containing 50wt% potassium hydroxide and 10wt% sodium carbonate and boiled for 8h. The casting is alternately treated with alkaline and acid solutions until the core is completely removed.

[0137] Comparative Example 10

[0138] The removal of silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0139] (1) using the silicon-based ceramic core prepared in Example 2 as a template to perform titanium alloy simulation casting to obtain a casting;

[0140] (2) immersing the casting in a mixed solution containing 50 wt% potassium hydroxide and 10 wt% sodium carbonate and boiling for 8 hours at a pressure of natural atmospheric pressure, while ultrasonically subjecting the casting;

[0141] (3) Take out the casting and soak it repeatedly in deionized water to remove the residual alkali solution;

[0142] (4) immersing the casting treated in step (3) in a 6 mol / L hydrochloric acid solution and keeping the temperature at 90° C. for 4 hours, while performing ultrasonic treatment on the casting;

[0143] (5) The casting is taken out and repeatedly soaked in deionized water, and then placed in a mixed solution containing 50wt% potassium hydroxide and 10wt% sodium carbonate and boiled for 8h. The casting is alternately treated with alkaline and acid solutions until the core is completely removed.

[0144] Comparative Example 11

[0145] The removal of silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0146] (1) using the silicon-based ceramic core prepared in Example 2 as a template to simulate the pouring of titanium alloy to obtain a casting;

[0147] (2) immersing the casting in a mixed solution containing 30 wt % potassium hydroxide and 10 wt % sodium carbonate and boiling for 8 hours at a pressure of natural atmospheric pressure, while ultrasonically subjecting the casting;

[0148] (3) Take out the casting and soak it repeatedly in deionized water to remove the residual alkali solution;

[0149] (4) Immerse the casting treated in step (3) in a hydrochloric acid solution containing copper chloride and nasturtium orange, keep the temperature at 90° C. for 4 hours, and simultaneously perform ultrasound on the casting. The concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10 g / L, 1 mmol / L, and 6 mol / L, respectively;

[0150] (5) The casting is taken out and repeatedly soaked in deionized water, and then immersed in a mixed solution of 30wt% potassium hydroxide and 10wt% sodium carbonate and boiled for 8 hours. The casting is alternately treated with alkaline and acid solutions until the core is completely removed.

[0151] Comparative Example 12

[0152] The removal of silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0153] (1) using the silicon-based ceramic core prepared in Example 2 as a template to perform titanium alloy simulation casting to obtain a casting;

[0154] (2) immersing the casting in a mixed solution containing 50 wt% potassium hydroxide and 5 wt% sodium carbonate and boiling for 8 h at a natural atmospheric pressure, while ultrasonically subjecting the casting;

[0155] (3) Take out the casting and soak it repeatedly in deionized water to remove the residual alkali solution;

[0156] (4) immersing the casting treated in step (3) in a hydrochloric acid solution containing copper chloride and nasturtium orange, keeping the temperature at 90° C. for 4 hours, and simultaneously performing ultrasonic treatment on the casting; wherein the concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10 g / L, 1 mmol / L, and 6 mol / L, respectively;

[0157] (5) The casting is taken out and repeatedly soaked in deionized water, and then placed in a mixed solution containing 50wt% potassium hydroxide and 5wt% sodium carbonate and boiled for 8h. The casting is alternately treated with alkaline and acid solutions until the core is completely removed.

[0158] Comparative Example 13

[0159] The removal of silicon-based ceramic core for titanium alloy casting comprises the following steps:

[0160] (1) using the silicon-based ceramic core prepared in Example 2 as a template to perform titanium alloy simulation casting to obtain a casting;

[0161] (2) immersing the casting in a 50 wt % potassium hydroxide solution and boiling it for 8 h at a natural atmospheric pressure, while ultrasonically treating the casting;

[0162] (3) Take out the casting and soak it repeatedly in deionized water to remove the residual alkali solution;

[0163] (4) Immersing the casting in a hydrochloric acid solution containing copper chloride and nasturtium orange, keeping the temperature at 90° C. for 4 h, and simultaneously subjecting the casting to ultrasonic treatment; wherein the concentrations of copper chloride, nasturtium orange, and hydrochloric acid are 10 g / L, 1 mmol / L, and 6 mol / L, respectively.

[0164] (5) The casting is taken out and repeatedly soaked in deionized water, and then placed in a 50wt% potassium hydroxide solution and boiled for 8 hours. The casting is alternately treated with alkaline and acid solutions until the core is completely removed.

[0165] The silicon-based ceramics and titanium alloy casting silicon-based ceramic cores prepared in Examples 1-2 and Comparative Examples 1-8 were tested for product expansion rate, open porosity, room temperature strength, high temperature strength, and inertness to titanium alloy reaction. The results are shown in Table 1:

[0166] Table 1

[0167]

[0168]

[0169] It can be seen from Table 1 that the addition of two mineralizers at the same time can significantly improve the room temperature strength, high temperature strength and open porosity of the ceramic core; and when the thickness of the yttrium oxide coating is greater than 100 μm, it can play a good isolation role and prevent the reaction between the silicon-based ceramic core and the titanium alloy.

[0170] The silicon-based ceramic core for titanium alloy casting prepared in Example 2 was removed by the removal methods of Example 3 and Comparative Examples 9-13, and the complete removal time of each group was recorded. The results are shown in Table 2:

[0171] Table 2

[0172] Complete core removal time (h) Alkali solution changes Acid changes Example 3 36 White turbidity Brown turbid solution Comparative Example 9 48 White turbidity Brown turbid solution Comparative Example 10 36 White turbidity Black turbid solution Comparative Example 11 48 White turbidity Brown turbid solution Comparative Example 12 48 White turbidity Brown turbid solution Comparative Example 13 60 White turbidity Brown turbid solution

[0173] It can be seen from Table 2 that the ceramic core can be effectively removed by combining alternating high-temperature immersion in alkali and acid solutions with ultrasonic dispersion, increasing the concentration of potassium hydroxide and adding sodium carbonate can effectively shorten the core removal time, and the use of a composite corrosion inhibitor can effectively inhibit the corrosion of titanium alloy by high-concentration hydrochloric acid.

[0174] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0175] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high porosity and high strength silicon-based ceramic, characterized in that: The raw materials of the silicon-based ceramic include solid powder and a binder. The solid powder is composed of the following components by weight percentage: composition: Silicon dioxide 60-100wt% Kaolin 0-20wt% Calcium hydroxide 0-20wt%; Among them, the content of kaolin is greater than 0, and the content of calcium hydroxide is greater than 0; The mass ratio of the solid powder to the binder is 1:0.01-0.

05.

2. The high porosity and high strength silicon-based ceramic according to claim 1, characterized in that: The average particle size of the silicon dioxide is 25-40 μm; the average particle size of the kaolin is 0.5-5 μm; and the average particle size of the calcium hydroxide is 0.5-2 μm.

3. The method for preparing the high-porosity and high-strength silicon-based ceramic according to claim 1 or 2, characterized in that: The following steps are involved: Silicon dioxide, kaolin and calcium hydroxide powders are mixed evenly to obtain a mixed powder; then a binder aqueous solution is added and mixed evenly; then pressed and formed to obtain a green body; after the green body is dried, it is sintered to obtain a silicon-based ceramic; finally, an yttrium oxide coating is sprayed on the surface of the silicon-based ceramic to obtain the silicon-based ceramic.

4. The method for preparing high-porosity and high-strength silicon-based ceramics according to claim 3, characterized in that: The sintering temperature is 1250-1450° C.; and / or the heat preservation sintering time is 3-6 hours.

5. The method for preparing high-porosity and high-strength silicon-based ceramics according to claim 3, characterized in that: The binder is polyvinyl alcohol; the concentration of the binder aqueous solution is 3-10wt%.

6. The method for preparing high-porosity and high-strength silicon-based ceramics according to claim 3, characterized in that: The solid-to-liquid ratio of the mixed powder to the binder aqueous solution is 15-20 g:1-3 mL.

7. The method for preparing high-porosity and high-strength silicon-based ceramics according to any one of claims 3 to 6, characterized in that: The following steps are involved: S1. Mix silicon dioxide powder, kaolin powder and calcium hydroxide powder evenly, and fully dry them at a temperature of 100-120°C; S2, ball milling the dried powder to obtain a mixed powder; wherein the ball-to-powder ratio is 2:1; S3, adding a binder solution to the mixed powder, mixing evenly and passing through a 100 mesh sieve; wherein the solid-liquid ratio is 15-20g:1-3mL; S4, taking the powder under the sieve and placing it in a mold for pressing, the pressure used is 3-10MPa, and the holding time is 30-60s to obtain a green body; S5, fully drying the green body at a temperature of 100-120° C.; S6. Place the dried green body in a muffle furnace and sinter it at a temperature of 1250-1450° C. to obtain the silicon-based ceramic.

8. A ceramic core for titanium alloy casting, characterized in that: It comprises a silicon-based ceramic and a coating on the silicon-based ceramic, wherein the silicon-based ceramic is the silicon-based ceramic according to any one of claims 1-2 or the silicon-based ceramic obtained by the preparation method according to any one of claims 3-7; and the coating comprises yttrium oxide.

9. The method for preparing a ceramic core for titanium alloy casting according to claim 8, characterized in that: The following steps are involved: The silicon-based ceramic is prepared according to the preparation method according to any one of claims 3 to 7, and then an yttrium oxide coating is sprayed on the surface of the silicon-based ceramic to obtain the ceramic core.

10. A method for removing a ceramic core for titanium alloy casting, characterized in that: The following steps are involved: (1) using the ceramic core according to claim 8 or the ceramic core obtained by the preparation method according to claim 9 as a template to cast a titanium alloy to obtain a casting; (2) placing the casting with the silicon-based ceramic core in a mixed alkali solution and boiling it, while simultaneously subjecting the casting to ultrasonic treatment; (3) After cooling, take out the casting and soak it in water to remove the residual alkali solution; (4) immersing the casting treated in step (3) in a hydrochloric acid solution containing a corrosion inhibitor, reacting at a temperature of 80-100° C., and simultaneously performing ultrasonic treatment; (5) Repeat steps (2) to (4) until the ceramic core is completely removed.

Citation Information

Patent Citations

  • Method for producing silicon-based ceramic core for aircraft engine blade

    CN102079653A

  • Method for preparing composite ceramic core

    CN103242036A

  • Method for preparing silicon oxide-based ceramic core for titanium and titanium alloy casting

    CN103693976A

  • Preparation method of shell synchronously modified by mineralizing agent and chopped carbon fibers

    CN106518027A

  • Aqueous chrome-free zinc-aluminum coating material, preparation method and applications thereof

    CN107722765A

Cited By

  • Preparation method of high-entropy rare earth silicate coated particle reinforced silicon-based ceramic core

    CN121735629A